DEVELOPMENT OF SOCIAL LITERACY SKILLS OF ELEMENTARY SCHOOL STUDENTS BASED ON THE LOCAL WISDOM OF REJANG LEBONG - Nasution, Aida Rahmi; Ratnawati, Ratnawati; Syarfuni, Syarfuni; Supriatin, Atin (UIN Sunan Kalijaga Yogyakarta, 2023)
The development of social literacy skills in learning appears to meet the need to improve students’ knowledge based on local wisdom. This study aims to develop students’ social literacy skills in social science lessons based on local wisdom at Elementary School 88 in Rejang Lebong. The research method used a Research and Development (R&D) approach adopted from ADDIE, that includes the stages of analysis, design, development, implementation, and evaluation. The samples were the teachers and fifth-grade students. The data collection techniques were interviews, questionnaires, and documentation. The qualitative data was analyzed through data collection, interpretation, verification, and conclusions. The quantitative data was analyzed using the percentage formula with intervals adopted from Hake. The research findings show that teachers and students need the development of social science leaning model based on local wisdom. The resulting material is suitable for use, and the test of the effectiveness of the learning model through small-group trials indicates that the model is effective in increasing the social literacy of elementary school students.